2002
DOI: 10.1007/s11664-002-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copper grains in damascene trenches after rapid thermal processing or furnace anneals

Abstract: INTRODUCTIONCopper has ϳ40% lower electrical resistivity and about two orders of magnitude higher electromigration resistance than aluminum, 1,2 making it the metal of choice for high-performance interconnects at the 180-nm technology node and beyond. Understanding the relationship between interconnect metal microstructure and electrical properties can allow processing to be optimized to increase device yield and reliability. 3-6 This is particularly true for the electrochemically deposited Cu, the most practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…After 30 min annealing at 1035 °C, the grain sizes are in a millimeter scale. Although the Cu (111) and (001) containing facets are enlarged, there is no particular preference for the growth of low‐index crystallographic (111) or (001) grains, consistent with previous results . To further evaluate the stability of certain Cu grains, we repeated the annealing process after the orientation measurement in Figure b.…”
Section: Size Dependent Percentage Of Single‐crystal 6‐ and 4‐ Lobed supporting
confidence: 82%
See 1 more Smart Citation
“…After 30 min annealing at 1035 °C, the grain sizes are in a millimeter scale. Although the Cu (111) and (001) containing facets are enlarged, there is no particular preference for the growth of low‐index crystallographic (111) or (001) grains, consistent with previous results . To further evaluate the stability of certain Cu grains, we repeated the annealing process after the orientation measurement in Figure b.…”
Section: Size Dependent Percentage Of Single‐crystal 6‐ and 4‐ Lobed supporting
confidence: 82%
“…In addition to the size, the 6‐lobed graphene islands exhibit a higher single‐crystal percentage than that of the 4‐lobed islands as shown in Table . We suppose that this is related to the suppressed surface pre‐melting for the close‐packed Cu (111) plane as well as the possibility of a significantly decreased binding energy (calculated as 33 meV per carbon atom) between graphene and Cu (111) containing facets compared with the binding energy between graphene and individual Cu atoms (1.814–1.981 eV) that are more likely to be present in the disordered regions of the Cu surface . Due to the suppressed surface pre‐melting and the lower binding energy, the Cu (111) plane is more stable and the graphene islands should be less affected by the Cu grain evolution.…”
Section: Size Dependent Percentage Of Single‐crystal 6‐ and 4‐ Lobed mentioning
confidence: 99%
“…1(b), consistent with previous reports. 26,27 To study the subsequent thermal effect on Cu grains, a 10 min annealing at 1000 °C was performed for the graphene-Cu sample (Experimental section) after the orientation measurement in Fig. 1(b).…”
Section: Resultsmentioning
confidence: 99%
“…This is because the initial grain size of electroplated Cu is as small as few tens nanometer [1] and grain growth occurs under the confinement by predefined trenches. The final grain size of Cu lines after annealing is known to be about its dimension of width [2], thus strain by volume shrinkage is considerably developed during grain growth. For example, Lee et al [3] reported that the growth stress in their electroplated Cu films was as large as 120MPa.…”
Section: Introductionmentioning
confidence: 99%